2004
DOI: 10.1073/pnas.0403668101
|View full text |Cite
|
Sign up to set email alerts
|

EosFP, a fluorescent marker protein with UV-inducible green-to-red fluorescence conversion

Abstract: A gene encoding a fluorescent protein from the stony coral Lobophyllia hemprichii has been cloned in Escherichia coli and characterized by biochemical and biophysical methods. The protein, which we named EosFP, emits strong green fluorescence (516 nm) that changes to red (581 nm) upon near-UV irradiation at Ϸ390 nm because of a photo-induced modification involving a break in the peptide backbone next to the chromophore. Single-molecule fluorescence spectroscopy shows that the wild type of EosFP is tetrameric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
674
2
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 641 publications
(714 citation statements)
references
References 31 publications
18
674
2
6
Order By: Relevance
“…In an earlier paper (27), we have reported that H-NS appears as a few large and discrete clusters in cells when fused to mEos2, a previously reported monomeric version of the Eos fluorescent protein (14,16). We also observed similar results when H-NS was fused to PAmCherry (27), another previously reported monomeric PAFP.…”
Section: Dimerization Tendency Of Photoactivatable Fluorescent Proteinssupporting
confidence: 75%
See 1 more Smart Citation
“…In an earlier paper (27), we have reported that H-NS appears as a few large and discrete clusters in cells when fused to mEos2, a previously reported monomeric version of the Eos fluorescent protein (14,16). We also observed similar results when H-NS was fused to PAmCherry (27), another previously reported monomeric PAFP.…”
Section: Dimerization Tendency Of Photoactivatable Fluorescent Proteinssupporting
confidence: 75%
“…Here, we compare four properties of PAFPs that are critical for superresolution imaging and report two new PAFPs that exhibit excellent performance in all four properties. (14), mEos3.2 (15), tdEos (16), mKikGR (17), PAmCherry (18), PAtagRFP (19), mMaple (20), PSCFP2 (13,21), Dronpa (22), and mGeosM (23). From this screen, we found that none of these PAFPs was simultaneously optimal in all four criteria described above.…”
mentioning
confidence: 87%
“…Photochromatism usually involves a two-step photooxidation process that causes cleavage of the polypeptide backbone (e.g. PSmOrange and EosFP [138,144]). Photoswitching involves cis-trans isomerisation of the chromophore accompanied by a change of its protonation state (the anionic state being the fluorescent state and the protonated the nonfluorescent-interestingly, the chromophore can be fluorescent in both the cis and the trans conformations as long as the protein scaffold keeps it in a planar conformation) [145][146][147].…”
Section: Fluorescent Probes For Localisation Microscopymentioning
confidence: 99%
“…In another group of FPs, the p-HBI chromophore can be converted irreversibly from a green to a red fluorescent state by a photochemical modification of the peptide backbone. In EosFP, Kaede and several other anthozoan FPs and variants, irradiation with 400 nm results in a cleavage of the peptide backbone between N a and C a of the first chromophore-forming residue histidine (63)(64)(65)(66)(67). Thereby, the conjugated p-electron system is extended in the imidazole sidechain of histidine.…”
Section: Light-induced Activation Of the Chromophorementioning
confidence: 99%
“…Great experimental opportunities arise from the diversity of fluorophores for multicolor labeling of proteins, cellular compartments or cells as well as for novel sensors based on fluorescence resonance energy transfer between FPs of different colors (8,39,57,66). Currently, at least five differently colored FPs can be imaged in parallel (8,59).…”
Section: Modifications Of the Gfp Chromophore And Its Environment Promentioning
confidence: 99%